Strength of Concrete Containing POFA and Fine Recycle Concrete as Partial Cement Replacement - Johan, Nur Hannis Sabrina; Sheikh Khalid, Faisal (Recent Trends in Civil Engineering and Built Environment, 2023)
Construction and industrial waste consumption has increased rapidly over the world in recent years, resulting in significant amounts of waste. It reflected the issue of a limited number of landfills due to the massive amount of waste created. One option is to recycle the waste and turn it into a useful product that will help to reduce landfill waste. As a result, the goal of this research is to study into the density, slump, compressive strength, and splitting tensile testing of concrete incorporating palm oil fuel ash (POFA) and fine recycled concrete wastes. Concrete was designed at 30 MPa, water cement ratio was 0.50 and containing 5%, 10% and 15% for both POFA and fine recycled concrete materials. At 7 and 28 days, compressive strength and density were tested, while splitting tensile strength was determined only at 28 days. The concrete containing 10% POFA and 10% FRCA was the ideally appropriate mix proportion to replace cement in concrete. In comparison to specimens that did not include POFA as a cement replacement, the addition of 10% POFA as a cement replacement increased the compressive strength and split tensile strength of concrete.